Peace in History and Heritage. Some thoughts on a Museum of Peace in Northern Ireland - Karine BIGAND (E-REA)
History, as an academic discipline, has traditionally focused more on conflict than on peace. Similarly, heritage, as an identity-marker, is rather exclusive than inclusive. In post-conflict Northern Ireland, the debate is ongoing about how to deal with the past, both in history-writing and in the heritage sector. The aims of this article are threefold. I would like to reflect on the methodological characteristics of academic history-writing and its tendency to leave peace out of the narrative. I would also like to present the problematic treatment of the Troubles in the post-conflict Northern Irish heritage sector. This will lead to exploring a shift in focus from war to peace in the representation of history, its modalities and consequences, through an imagined Museum of Peace in Northern Ireland.